2017
DOI: 10.7705/biomedica.v38i0.3609
|View full text |Cite
|
Sign up to set email alerts
|

Contaminación por mercurio de leche materna de madres lactantes de municipios de Antioquia con explotación minera de oro

Abstract: Introduction: Breast milk is essential for human development, but it may contain toxics derived from environmental pollution, especially in mining areas. Objective: To assess the prevalence of mercury contamination in breast milk and factors associated with its transfer to nursing mothers living in municipalities with gold mining. Materials and methods: We conducted a cross-sectional study with 150 nursing mothers in four municipalities of Antioquia (El Bagre, Segovia, Remedios and Zaragoza) with a mining trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…For this, each mother was asked to collect 15 milliliters of breast milk in test tubes at any time of the day. After analyzing the samples, it was found that 10.2% of the samples from Segovia exceeded the permissible limit for mercury, while in Remedios, it was 5.6% [21].…”
Section: Artisanal and Small-scale Gold Mining In Northeast Antioquiamentioning
confidence: 99%
See 3 more Smart Citations
“…For this, each mother was asked to collect 15 milliliters of breast milk in test tubes at any time of the day. After analyzing the samples, it was found that 10.2% of the samples from Segovia exceeded the permissible limit for mercury, while in Remedios, it was 5.6% [21].…”
Section: Artisanal and Small-scale Gold Mining In Northeast Antioquiamentioning
confidence: 99%
“…On the other hand, Molina et al [21] collected samples of breast milk from 50 mothers from Segovia and 17 mothers from Remedios to measure the concentration of mercury that was present in them. For this, each mother was asked to collect 15 milliliters of breast milk in test tubes at any time of the day.…”
Section: Artisanal and Small-scale Gold Mining In Northeast Antioquiamentioning
confidence: 99%
See 2 more Smart Citations
“…Según investigaciones, productos químicos como el mercurio no son fácilmente absorbidos por la piel o el tracto digestivo, pero sí cuando sus vapores son consumidos por vía pulmonar (onu, 2002). Adicionalmente, la exposición crónica al metilmercurio por consumo de peces y semillas con altas concentraciones puede ocasionar alteraciones sensitivas y motoras en el sistema nervioso central y en el cerebro, particularmente durante la infancia y la etapa prenatal, debido a que esta forma mercurial tiene la capacidad de atravesar rápidamente la barrera placentaria cuando el bebé está en formación o, posteriormente, ingresar al organismo del niño a través de la ingesta de leche materna (Molina, Arango & Sepúlveda, 2018;Güiza, 2011).…”
Section: Impactos Ambientalesunclassified